P099 Serum proteomic analysis reveals novel biomarkers associated with disease activity in pediatric patients with Crohn's disease. (21st January 2022) - Werner, L; Weiss, B; Matar, M; Shamir, R; Shouval, D
Abstract: Background: Although Crohn's disease (CD) is associated with a marked hyper-inflammatory response, identifying serum biomarkers associated with disease activity and outcomes is considered challenging, given lack of sensitivity of different assays. Our aim was to identify novel markers using Olink, a novel technology based on proximity extension assay, enabling detection of minute amounts of proteins. Methods: Serum samples were obtained from pediatric patients with CD at the time of diagnosis and following induction therapy, and from control subjects, consisting of pediatric patients with normal endoscopic procedures, without past or present history of an immune-mediated disorder (e.g. celiac, diabetes). Serums were subjected to Olink (two panels used, consisting of 184 proteins), and analysis was performed on a Normalized Protein eXpression file by supervised, multivariate, principal component analysis and verification by univariate ANOVA with Benjamini-Hochberg and post-hoc Tukey analysis. Results: Eighty-eight serum samples were collected: 30 from control subjects and 58 from 32 patients with CD (24 of them pre- and post-induction therapy). The median age of patients in the control and CD groups was 13.9 years (IQR 11.1–16.6) and 14.6 years (IQR 12.2–16.9), respectively (P=0.32). Twenty-four patients were treated with anti-TNFa agents and 8 with EEN. The median pediatric Crohn's Disease Activity Index (PCDAI) decreased from 35 (22.5–42.5) to 5 (0–12.5, P<0.001) following induction therapy. We identified 72 proteins that significantly differed between patients and controls, and many of them were associated with CRP or ESR levels. String analysis identified several important nodes linking different proteins, including MMPs, MPO, EGFR and TNFRSF1A. Many proteins, such as resistin and different MMPs, showed a strong positive correlation with disease activity, based on PCDAI, while others, such as EGFR, showed a negative correlation. Several novel markers were identified to be highly expressed in the serum of patients with CD, including LRIG1, an intestinal stem cell marker, that was highly correlated with disease activity among the patients. Conclusion: We identified novel serum markers that are associated with disease activity in pediatric patients with CD. These findings should be validated in future studies, and be complemented with expression and functional studies to define their role in mediating intestinal immune responses.